The Estimation of phytochemicals and study of biological activities of Leucas lavandulifolia sm’s (Gumma) leaf extract - Chauhan, Trichandra Prasad; Janak Lal Jaishi, Dipak Raj Jaishi; Ojha, Siddha Raj; Thapa, Manisha Kumari; Basnyat, Ram Chandra (BIBECHANA, 2026)
AbstractMedicinal Plants have a long history and have been used as medicinal agents to cure a variety of diseases. The main aim of this study is the investigation of the phytochemical profile and biological activity of leaf extracts of Leucas lavandulifolia, using methanol, ethanol, ethyl acetate, DCM and hexane as solvents. This study quantifies the total phenolic content (TPC), and total flavonoid content (TFC) of each extract. Additionally, antioxidant activity is evaluated using the DPPH radical scavenging test. The antibacterial effectiveness of various plant extracts is evaluated against a variety of pathogenic microorganisms along with the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) determined. The cytotoxic effects of the extracts are determined using the brine shrimp lethality test. The results show significant changes in phytochemical composition and biological activity. The methanol and ethyl acetate extracts had the highest TPC and TFC values (56.95 ± 0.13 mg GAE/g and 119.83 ± 0.12 mg QE/g, respectively), indicating a high abundance of polyphenolic compounds. The methanolic extract had high antioxidant activity (221.0 ± 0.15 µg/mL), whereas the ethyl acetate and hexane extracts showed weak antioxidant potential. Furthermore, the antibacterial activity of Ethyl acetate extract against S. aureus and S. sonnei were found to be 11 mm for both extracts. Which was slightly near to that of positive control neomycin (22 mm and 23 mm). Ethyl acetate and DCM extracts had equal MIC and MBC value against S. sonnei (MIC 1.56 mg/mL & MBC). The LC50 for DCM extract was found as 731.31 µg/mL. This extensive comparative analysis provides insight on the solvent-dependent extraction efficiency and biological activities of Leucas lavandulifolia extracts, laying the groundwork for future research and possible uses in medicines, nutraceuticals, and cosmetics.